Microbiological Profiles, Antibiotic Susceptibility Patterns and the Role of Multidrug-Resistant Organisms in Patients Diagnosed with Periprosthetic Joint Infection over 8 Years: Results from a Single-Center Observational Cohort Study from Romania - Serban Dragosloveanu; Rares-Mircea Birlutiu; Bogdan Neamtu; Victoria Birlutiu (Microorganisms)
This study examines temporal patterns in pathogens isolated from prosthetic joint infection (PJI) cases and antimicrobial resistance patterns at a Romanian orthopedic center. We have conducted a retrospective cohort study that included 674 patients undergoing hip or knee replacement revision surgery between January 2016 and December 2023. From these, 102 confirmed PJI cases requiring surgical intervention were selected for analysis. We isolated 27 microorganisms from acute PJI cultures and 82 from chronic PJIs. Staphylococcus epidermidis (33 cases, 30.3%; 95% CI 22.0–40.3) was the predominant pathogen, with coagulase-negative Staphylococci (22 cases, 20.18%; 95% CI 0.9–41.3) and Enterobacteriaceae (13 cases, 11.9%; 95% CI 6.4–18.3) also prevalent. Methicillin resistance was identified in 43.6% of coagulase-negative staphylococci and 45.5% of Staphylococcus aureus isolates. All Gram-positive isolates remained susceptible to vancomycin, linezolid, and tigecycline. Among Gram-negative bacilli, Klebsiella oxytoca and Proteus mirabilis showed resistance to third-generation cephalosporins, with phenotypic profiles suggestive of extended-spectrum β-lactamase (ESBL) production. All Escherichia coli, Enterobacter spp., and Citrobacter freundii strains were fully susceptible to tested agents, while Pseudomonas aeruginosa exhibited reduced susceptibility to ciprofloxacin, aztreonam, and imipenem. Among the isolated strains, 47 were multidrug-resistant (MDR), with Staphylococcus aureus accounting for the highest MDR count, including methicillin resistance. The distribution of microorganism types and MDR strains remained consistent throughout the study period, with no significant association between infection type and MDR strain presence or between infection site and microorganism presence except for a strong association between MDR strains and the type of microorganism (p < 0.05). The microbial profile and resistance patterns in PJIs have remained stable over eight years. Our observations do not suggest that MDR PJIs are more commonly acute cases, contrary to what has been highlighted in previous reports. The ongoing prevalence of MDR strains underscores the importance of targeted antimicrobial treatments based on local susceptibility profiles.